Web reflection: the design and implementation of a reflective journal using PebblePad - Richardson, Joan; Di Iorio, Amalia; Cerotti, Paul; Davison, Claire; Md Ali, Asma (2011)
International student mobility is high on the agenda of universities and governments worldwide. One model that enables the internationalization of tertiary programs is found in Study Tours, typically short-term programs of less than one semester and offered by many international universities. Study Tours combine both onshore and offshore learning and teaching activities designed to develop students’ professional and personal intercultural capabilities. In this paper a research project that resulted in the design, development and trialling of an online self-reflective journal for Study Tour students is described. Individual learning was described using a reflective journal that was part of the assessment for the subject. PebblePad was the vehicle used to record the reflective journal. The project allowed students to capture the learning experiences of living and studying in another country in real-time through a variety of modes including photos, videos and podcast, to organise and store their personal and professional development histories. The evaluation is guided by constructive alignment where the course objectives, learning activities and assessment task are aligned.